Integrated Design of MnO2@Carbon Hollow Nanoboxes to Synergistically Encapsulate Polysulfides for Empowering Lithium Sulfur Batteries. Issue 20 (31st March 2017) - Rehman, Sarish; Tang, Tianyu; Ali, Zeeshan; Huang, Xiaoxiao; Hou, Yanglong
Abstract : Lithium sulfur batteries (LSBs) with high theoretical energy density are being pursued as highly promising next‐generation large‐scale energy storage devices. However, its launch into practical application is still shackled by various challenges. A rational nanostructure of hollow carbon nanoboxes filled with birnessite‐type manganese oxide nanosheets (MnO2 @HCB) as a new class of molecularly‐designed physical and chemical trap for lithium polysulfides (Li2 S x ( x = 4–8)) is reported. The bifunctional, integrated, hybrid nanoboxes overcome the obstacles of low sulfur loading, poor conductivity, and redox shuttle of LSBs via effective physical confinement and chemical interaction. Benefiting from the synergistic encapsulation, the developed MnO2 @HCB/S hybrid nanoboxes with 67.9 wt% sulfur content deliver high specific capacity of 1042 mAh g −1 at the current density of 1 A g −1 with excellent Coulombic efficiency ≈100%, and retain improved reversible capacity during long term cycling at higher current densities. The developed strategy paves a new path for employing other metal oxides with unique architectures to boost the performance of LSBs. Abstract : A rational nanostructure of hollow carbon nanoboxes filled with birnessite‐type manganese oxide nanosheets (MnO2 @HCB) has been fabricated to overcome the obstacles of low sulfur loading, poor conductivity, and redox shuttle of lithium sulfur batteries (LSBs) via effective physical confinement and chemical interaction to enhance the electrochemical performance of LSBs.